A Cross Sectional Study to Evaluate Tree Plantation and Gardening as an Intergenerational Bonding Activity Amongst Geriatric Population (Indian Journal of Public Health Research & Development, 2020)
Background: Life expectancy among the elderly has been improving for many decades all over world, theemotional and mental wellbeing of the geriatric people is at stake because of the younger people migratingto the urban areas or even abroad for work, and older people staying alone at their homes.Few days can be spent by older–younger people together to plant trees. And this intergenerational bondingactivity can give a sense of satisfaction and mental wellbeing to the older adults.Objectives:1. To find out how older people spend time with younger generations2. To evaluate if older people are interested in gardening and planting trees as an intergenerational activity.Method: We conducted a survey on 120 older people in the community attached to our college, we enquiredabout the different means by which the older people spend time with the younger generations and if they willbe interested in gardening or planting trees together with the younger generations.Results: There were a total of 120 participants, 60 males and 60 females. Mean age was 68.49 ± 6.83years. Majority of them interacted with the younger generations daily (55.83%). Chit chatting, managingbusiness and telling stories to children were the common things done together. Majority (70%) felt that theyspent enough time with the younger people, while few were not spending time at all with their youngergenerations (5.83%). 79 participants never planted a single tree (65.83%). 107 participants felt that plantingtrees is necessary (89.17%) while 104 participants (86.67%) would like to do gardening or planting treeswith their younger generations.
Keywords: Intergenerational Activities, Geriatric Mental Health, Tree Plantation